2003
DOI: 10.1046/j.1600-0854.2003.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐1 Egress is Gated Through Late Endosomal Membranes

Abstract: HIV‐1 buds from the surface of activated T lymphocytes. In macrophages, however, newly formed HIV‐1 particles amass in the lumen of an intracellular compartment. Here, we demonstrate by live‐cell imaging techniques, by immunocytochemistry and by immuno‐electron microscopy that HIV‐1 structural proteins, particularly the internal structural protein Gag, accumulate at membranes of the late endocytic compartment in a variety of cell types and not just in monocyte/macrophage‐derived cells. Recent biochemical and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
168
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(189 citation statements)
references
References 54 publications
19
168
2
Order By: Relevance
“…2) led us to test the hypothesis that the mechanism of virus transfer mediated by DCs could involve exocytosis of vesicles (exosomes) bearing captured HIV-1 particles. Exocytosis has also been demonstrated as a mechanism for virus particle release from productively infected macrophages, especially for those viral capsids that assemble at internal endosomal membranes of the MVB (22)(23)(24). Alternatively, in the case of DCs, HIV capture and endoyctosis to MVBs could also result in an association of infectious particles with exocytic vesicles that express MHC Class II and tetraspan proteins on the vesicle surface and could be released to the extracellular environment upon fusion of MVB with the plasma membrane.…”
Section: Hiv-1 Particles Released Into Cell-free Supernatants Are Infmentioning
confidence: 99%
“…2) led us to test the hypothesis that the mechanism of virus transfer mediated by DCs could involve exocytosis of vesicles (exosomes) bearing captured HIV-1 particles. Exocytosis has also been demonstrated as a mechanism for virus particle release from productively infected macrophages, especially for those viral capsids that assemble at internal endosomal membranes of the MVB (22)(23)(24). Alternatively, in the case of DCs, HIV capture and endoyctosis to MVBs could also result in an association of infectious particles with exocytic vesicles that express MHC Class II and tetraspan proteins on the vesicle surface and could be released to the extracellular environment upon fusion of MVB with the plasma membrane.…”
Section: Hiv-1 Particles Released Into Cell-free Supernatants Are Infmentioning
confidence: 99%
“…Viral components are assembled in late endosomes/multivescicular bodies (MVB) in macrophages (Pelchen-Matthews et al, 2003;Raposo et al, 2002). Gag targeting and HIV-1 assembly have been suggested to occur in late MVB in macrophages and in other cells including CD4+ T lymphocytes (Nydegger et al, 2003). However, other authors suggested that the targeting of Gag to the plasma membrane in T cells or to MVB in macrophages involves different signals (Ono and Freed, 2004).…”
Section: Virus Assembly and Releasementioning
confidence: 99%
“…Late endosomes also fuse to the plasma membrane and may release virus particles into the external medium (Nydegger et al, 2003). In macrophages, viruses can also bud to the lumen of endocytic organelles (Pelchen-Matthews et al, 2003).…”
Section: Virus Assembly and Releasementioning
confidence: 99%
“…However, the biological significance of these inclusions in RDV infection has not been clarified because, for the most part, the tissues examined were in the late stage of infection which made it difficult to gather details on the formation of these compartments. Similar vesicular compartments appear to play a role in the release of viral particles from cultured cells infected with animal viruses, such as severe acute respiratory syndrome coronavirus (Ng et al, 2003) and human immunodeficiency virus (HIV) (Nydegger et al, 2003).A method for the continuous culture of cells from the leafhopper vector Nephotettix cincticeps, consisting of VCMs, has allowed the study of infection with RDV because such infection results in asymptomatic but persistent infection (Peterson & Nuss, 1985;Kimura, 1986). VCMs have been used to reveal fundamental aspects of viral activity at the cellular level, which suggests details of the transmission, multiplication and cytopathology of RDV in vector insects (Wei et al, 2006a(Wei et al, , b, c, 2007(Wei et al, , 2008.…”
mentioning
confidence: 99%
“…However, the biological significance of these inclusions in RDV infection has not been clarified because, for the most part, the tissues examined were in the late stage of infection which made it difficult to gather details on the formation of these compartments. Similar vesicular compartments appear to play a role in the release of viral particles from cultured cells infected with animal viruses, such as severe acute respiratory syndrome coronavirus (Ng et al, 2003) and human immunodeficiency virus (HIV) (Nydegger et al, 2003).…”
mentioning
confidence: 99%